PEMANFAATAN NEMATODA PATOGEN Steinernema spp. Isolat Malang Dan Nusa Tenggara Barat DALAM PENGENDALIAN Spodoptera litura L. YANG RAMAH LINGKUNGAN - Heri Prabowo (Bumi Lestari Journal of Environment, 2012)
Research was conducted at Laboratory of Insect Pathology, Indonesian Tobacco and FiberCrops Research Institute, Malang. Research was conducted from July-August 2009. Isolatesof Steinernema spp. used is a collection of Insect Pathology Laboratory. Research arrangedin a Completely Randomized Design (CRD) with repeated 4 times. The research was conductedby using 4 concentrations of 0, 100, 200, and 300 IJ / ml. Each concentration was tested on 25insects. Observation of dead insects after 24 to 96 hours after infestation. Parameter larvalweight was observed 96 hours after treatment. Steinernema spp. West Nusa Tenggara andMalang isolates capable of causing mortality S.litura instar two ranges 4-78% for 96 hoursafter treatment. With the increasing concentration of Steinernema spp. given will increase themortality of S. litura. Provision of Steinernema spp. at various concentrations capable inhibitthe weight of larvae. Steinernema spp. has potential to be developed as bioinsecticide.